Twist and shout: magnetic resonance imaging findings in ovarian torsion - Gomes,Matheus Menezes (2019)
Abstract Adnexal torsion is characterized by partial or complete rotation of the suspensory ligament of the ovary and its corresponding vascular pedicle, resulting in vascular impairment that can culminate in hemorrhagic infarction, as well as necrosis of the ovary and fallopian tube. Because there are myriad causes of acute pelvic pain, the differential diagnosis of ovarian torsion is often challenging. Consequently, radiologists should be familiar with the main imaging findings. In this regard, there are typical signs of ovarian torsion on magnetic resonance imaging, including increased ovarian volume with stromal edema and peripheral distribution of the ovarian follicles, as well as thickening of the fallopian tube, an adnexal mass (causal factor) that shifts toward the midline, and the classic, pathognomonic “whirlpool sign”. The objective of this essay was to review and illustrate the various magnetic resonance imaging findings in ovarian torsion.